Macroeconomic variables affect stock market Malaysia / Nurul Aini Ahmad Shukri - Ahmad Shukri, Nurul Aini (2017)
The relationship between performance of stock market and macroeconomic variables has been a focus of many empirical studies. Several methods have been used to measure the performance of stock market towards the macroeconomic variables. This paper investigates the relationship between Kuala Lumpur Composite Index Market with three selected macroeconomic variables; inflation rate, money supply, and interest rate based on monthly data from 2010 to 2016. The methodology used in this study is time series econometric techniques. The results suggest that Malaysian stock market has strong interaction with money supply as compared to interest rate and inflation rate.